Heavy metals emissions from joss paper burning rituals and the air quality around a specific incinerator. (2021) - Giang, Lam Van; Thanh, Tran; Hien, Truong Thanh; Tan, Lam Van; Thi Bich Phuong, Tran; Huu Loc, Ho
Abstract: Burning joss paper is a traditional and long-term historical custom in Oriental countries. However, joss paper contains a lot of toxic components [1], which can be released into the environment during the burning stage [2, 3] and caused health risk [4] . The objective of this study is to assess the heavy metals in bottom ash and dust fume by using a burning chamber in the laboratory; thereby, it also assesses the ambient air from the incinerator – a case study at Thien Hau pagoda, District 5, HCM city. The initial result showed that there is a significant amount of heavy metals in the dust fume and bottom ash in order Al < Fe < Mn < Cu < Pb < Zn < Cd. The result of analyzing metal contents in ash samples from T1 to T4 showed that all is higher than Vietnam Standard (QCVN 03:2008/BTNMT – National technical regulation on the allowable limits of heavy metals in the soils [5] ) with 236.21 ppm Cu, 4.93 ppm Cd, and 128 ppm Pb. Moreover, the results of assessing the ambient air quality at a pagoda indicated that the incinerator (S3) was the source with the highest of dust concentration and had a significant impact on air quality to the location around.